The contribution of haemoglobin mass to altitude induced increases in 4 minute cycling power - Garvican, L.; Pottgiesser, T.; Martin, D. T.; Barras, M.; Fallon, K.; Schumacher, Y. O.; Hore, C. J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Sleeping at altitude and training at sea level (LHTL) is a popular training strategy for elite endurance athletes aiming to improve their performance at sea level. Although the primary mechanism by which LHTL improves performance is still debated,1 the popular paradigm suggests that improvements in sea level performance are primarily due to improvements in aerobic power, via an erythropoietin induced increase in haemoglobin mass (Hbmass). However, research from our lab and others suggests that other non-haematological adaptations may be equally, if not more important.2 We sought to determine whether the altitude induced improvement in sea level performance was still present if the altitude induced increase in Hbmass was removed. Methods 14 national-level female cyclists completed 26 nights of simulated altitude exposure (>14 h.d-1, 3000 m) during a cycling training camp. Hbmass was determined from the mean of four measures before, and of duplicate measures during, each week of LHTL using the carbon monoxide rebreathing method.3 Cyclists were pair matched after 14 nights of LHTL based on their altitude induced Hbmass increases and divided into two groups: an altitude group (Hbmass +, n=5) in which Hbmass was free to adapt, and a clamp group (Hbmass 0, n=6) in which any increase in Hbmass was removed to ensure that Hbmass for each individual at the end of the altitude period was equal to baseline. The volume of blood to be removed from the clamp group was calculated as follows: Volume venous removed (mL) = Change in Hbmass from baseline (g) / (Hb concentration (g.dL-1) / 100 (mL /dL)) Hb concentration was determined from venous blood sampled immediately prior to blood withdrawal. All cyclists were unaware of the volume of blood removed. Cyclists in the altitude group received a `sham` withdrawal of a similar standardised duration. Cycling performance (maximal mean power) and maximal aerobic power (VO2peak) were assessed during a maximal four minute cycling effort performed on an electromagnetically braked cycle ergometer, in duplicate before and after the altitude camp. Data were analysed using a contemporary approach,4 with data log-transformed prior to analysis to reduce any bias arising from non-uniformity of error. Mean effects were estimated via the unequal-variances t statistic computed for change scores between pre- and post-tests. Linear regression analysis was used to determine the relationship and correlation between changes in Hbmass and cycling performance, with a modified scale used to interpret the magnitude of correlations.4 Results 11 out of 14 cyclists fulfilled criteria for group allocation. An increase in Hbmass was observed in both groups (Mean ± SD, Hbmass + = 5.5 ± 2.9%, Hbmass 0 = 4.5 ± 2.1%). At the time of post-altitude testing, the mean change in Hbmass of the clamp group was = -0.4 ± 0.6%, and was "very likely" lower than Hbmass +. Maximal mean power during the four minute cycling test (MMP4min) improved in all athletes. Mean increases in both groups were: Hbmass+ = 4.4 ± 1.1%, Hbmass 0 = 3.6 ± 1.4%) with differences in the magnitude of change between the groups "possibly trivial". VO2peak increased in Hbmass + (3.5 ± 2.3%) but not in Hbmass 0 (-0.2 ± 2.6%) and was "very likely" higher in Hbmass +. There was a "large" correlation (r=0.6) between changes in Hbmass and MMP4min in Hbmass +, however, this relationship was not present in Hbmass 0 as shown in Figure 1. Discussion/Conclusion Improvements in cycling performance and VO2peak were observed in the altitude group who increased their Hbmass by ~5%, however, improvements in four minute cycling performance were also observed in the absence of an enhanced Hbmass or VO2peak. These novel findings question the popular belief that increases in Hbmass are a prerequisite for enhanced performance following altitude1 and suggest that accelerated erythropoiesis is not the sole mechanism by which altitude training improves performance.